Effect of translocation defective reverse transcriptase inhibitors on the activity of N348I, a connection subdomain drug resistant HIV-1 reverse transcriptase mutant - Michailidis, E.; Singh, K.; Ryan, E. M.; Hachiya, A.; Ong, Y. T.; Kirby, K. A.; Marchand, B.; Kodama, E. N.; Mitsuya, H.; Parniak, M. A.; Sarafianos, S. G. (Cellular and Molecular Biology, 2012)
4’-Ethynyl-2-fluoro-2’-deoxyadenosine (EFdA) is a highly potent inhibitor of HIV-1 reverse transcriptase (RT). We have previously shown that its exceptional antiviral activity stems from a unique mechanism of action that is based primarily on blocking translocation of RT; therefore we named EFdA a Translocation Defective RT Inhibitor (TDRTI). The N348I mutation at the connection subdomain (CS) of HIV-1 RT confers clinically significant resistance to both nucleoside (NRTIs) and non-nucleoside RT inhibitors (NNRTIs). In this study we tested EFdA-triphosphate (TP) together with a related compound, ENdA-TP (4’-ethynyl-2-amino-2’-deoxyadenosine triphosphate) against HIV-1 RTs that carry clinically relevant drug resistance mutations: N348I,D67N/K70R/L210Q/T215F, D67N/K70R/L210Q/T215F/N348I, and A62V/V75I/F77L/F116Y/Q151M. We demonstrate that these enzymes remain susceptible to TDRTIs. Similar to WT RT, the N348I RT is inhibited by EFdA mainly at the point of incorporation through decreased translocation. In addition, the N348I substitution decreases the RNase H cleavage of DNA terminated with EFdA-MP (T/PEFdA-MP). Moreover, N348I RT unblocks EFdA-terminated primers with similar efficiency as the WT enzyme, and further enhances EFdA unblocking in the background of AZT-resistance mutations. This study provides biochemical insights into the mechanism of inhibition of N348I RT by TDRTIs and highlights the excellent efficacy of this class of inhibitors against WT and drug-resistant HIV-1 RTs.